Study on effect of laser keyhole weld termination regimes and material composition on weld overlap start-stop defects - Lai, Wai Jun; Ganguly, Supriyo; Suder, Wojciech (Elsevier, 2020)
The effects of two different laser termination regimes; laser power ramp-down and laser defocusing, on the weld overlap start-stop region, have been studied on three different compositions of S355J2+N grade steel plates. The plates have varying amounts of deoxidisers, such as manganese and silicon, to allow for the effect of dissolved oxygen on melt pool dynamics and defect formation to be studied. Observations show that gas entrapment, manifesting as porosity, is the main issue in both the laser termination regimes studied, due to melt pool instabilities related to keyhole termination. However, it is more severe during laser defocusing due to the formation of porosity clusters below a specific power density and melt pool size. The percentage of dissolved oxygen and deoxidisers was found to be vital and could be correlated to the response of the melt pool during laser processing. Steel, with a higher percentage of deoxidisers, such as manganese and silicon, would combine with the dissolved oxygen in the weld pool and thereby affect the surface tension and melt pool dynamics. The effect of lower dissolved oxygen would lead to a reduction in penetration depth, but more importantly, porosity and porosity cluster formation, as observed for both laser termination regimes. Successful laser termination with defect-free weld overlaps at the start-stop region could be achieved using both termination regimes for the steel with a higher proportion of deoxidising elements
Keywords: Laser defocusing; Laser power ramp-down; Laser keyhole welding